Place matters: geographers and gang members - Bloch, Stefano (The Oxford handbook of gangs and society, 2024)
Research on place-making and place-taking coming out of the discipline of geography remains an untapped intellectual resource for research on gangs. Part of the reason for this is that geographers have not sufficiently included gangs and gang members in their theories of space and place. This may be surprising given what is known about gangs and their place-oriented penchant for territoriality and neighborhood demarcation as part of their expressed raison d’être. This chapter brings geography further into the conversation on gangs that criminologists and sociologists have been having for decades, concluding with personal reflection and a discussion about how to make geography a home for gang studies.